PERANGKAT LUNAK KEAMANAN BERBASIS FILE MENGGUNAKAN ALGORITMA KRIPTOGRAFI VIGENERE CIPHER - Susanto, Edi; Rizki, Sestri Novia (Computer Science and Industrial Engineering, 2021)
Security is an important aspect of an information system. Many people do not know how to secure files that are created or received or do not know how to protect files that are created or received so that there is no theft of files that cause information from those files to leak. Every organization, industry, or infrastructure, needs a level of network security solution to protect against the growing hacker threats in today's world. Text files that contain information in text form. Data originating from word processing documents, numbers used in calculations, names and addresses in the database are examples of text data input consisting of characters, numbers and punctuation marks. Input and output text data is represented as a character set or code system recognized by the computer system. Cryptography is a science that studies how to keep data safe when sent, from sender to receiver without experiencing interference from third parties. Vigenere Cipher is method of encrypting alphabetic text using letter and numbers. This table is usually referred to as the Vigenere Table. The concept of cryptography itself has long been used by humans, for example in the Egyptian and Roman civilizations, although it is still very simple.